Penerapan Emotional Connection Dalam Perancangan Board Game Edukatif Bertema Konservasi Badak Jawa - Gadri, Rafie Maulana Yusuf; Sujatmiko, Guguh; Cintya, Hedi Amelia Bella (SPACEPRO: Product Design Jurnal, 2025)
This study focuses on the application of emotional connection in the design process of a board game themed around Javan rhino conservation as an educational medium for teenagers. Rather than emphasizing a finalized product, the research positions the design process as a reflective medium to explore how emotional approaches can foster empathy toward environmental issues. The study employs a design research approach with a descriptive qualitative method through literature review, field observation, and interviews with three officers from Ujung Kulon National Park. The game mechanics were developed through a dual role systemconservation and hunter teamsrepresenting the value conflict between preservation and exploitation of nature. The findings reveal that the implementation of emotional connection at both narrative and social levels enhances players’ emotional engagement, even without a finalized visual prototype. This study affirms that design functions as a reflective practice integrating empathy, social awareness, and ecological values. Conceptually, it contributes to the discourse of design for empathy and demonstrates the potential of board games as educational media that encourage moral reflection and ecological awareness.